The sheep industry in Kansas - Kramer, George Otto (My University, 1905)
Introduction: The sheep industry is at present receiving very little attention among the Kansas farmers as compared with what it did twenty years ago. In 1884 the number of sheep in Kansas was 1,206,297, but from that time until 1895 when the number re ached 136,520, there was a constant and steady decrease as shown by the figures, and the census of 1904 showed a total of only 167,721. Owing to the favorable climatical and food conditions prevailing in Kansas it is difficult to account for this decrease. However, there were certain conditions of environment which prevailed two decades ago, which undoubtedly had an influence in driving out the sheep industry. The first was the presence of a large number of dogs of worthless character, whose deadly work was surpassed only by that of the countless number of wolves that everywhere flourished off the flocks of the farmers. The country being undeveloped, especially in Western Kansas, as far as improvement s are concerned, sufficient protection was not furnished the sheep at night, and. Watching them night and day added much to thjLe9 2apense of raising them. In conformation to these facts the following statement, taken from the Secretary of Agriculture in 1873, are given: "Mr. H. J. Stevens, of Newberry, Kansas, in reply to an inquiry from the secretary of the Board says: 'Kansas is a state as well adapted to the sheep industry, and in Wabaunsee county we raise wool and mutton for 50 per cent less than in the state of Ohio. But in. other localities we need protection against the worthless dogs." In the same report James O'Neil, of Jefferson county, Kansas, says: “imported in 1869 one hundred and fifty of the best long-wooled Cotswold and Leicester sheep.
Citation: Kramer, George Otto. The sheep industry in Kansas. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Ideal Climate; Location for Marketing; Feed; Theses